THER-29. NOVEL DUAL EGFR/PI3-KINASE INHIBITORS SHOW ENHANCED POTENCY, STRONGER PATHWAY SUPPRESSION AND TARGETING OF METABOLIC PROPERTIES IN PEDIATRIC AND ADULT HIGH GRADE GLIOMA MODELS THAN SINGLE KINASE INHIBITORS. (23rd April 2019) - Sun, Yusha; Bailey, Cavan; Whitehead, Christopher; Sebolt-Leopold, Judith; Chandra, Joya
Abstract: High grade gliomas (HGG), including glioblastoma (GBM) and diffuse intrinsic pontine glioma (DIPG), carry poor prognosis with median survival rates under 15 months post diagnosis. Due to dysregulation of the RTK/PI3K pathways within these tumors, targeted kinase inhibition has been considered a promising strategy to improve patient outcomes. However, many single-agent inhibitors of EGFR or PI3K have shown limited response in gliomas due to poor blood-brain barrier (BBB) penetrance and activation of compensatory signaling. Single-molecule multikinase inhibitors may decrease resistance, present a single pharmacokinetic dosage profile, and reduce risks of multi-agent toxicities, supporting this strategy over dual drug combination approaches. A panel of inhibitors exploiting known binding modes of structurally-related ATP binding site inhibitors of EGFR/PI3K were synthesized and characterized, of which six promising candidates were chosen for in vitro study. Of the compounds, MTX-241 was least likely to act as a substrate for drug efflux proteins such as P-glycoprotein. Treatment of MTX-241 in three patient-derived DIPG lines, and two glioma stem cell (GSC) lines, showed strong cytotoxic potency measured by growth inhibitory activity, with IC50 s in the µM range. MTX-241 was significantly more potent than clinically relevant inhibitors targeting EGFR/RTKs (gefitinib, lapatinib, dasatinib, imatinib) or PI3K (alpelisib, idelalisib). Notably, selectivity of MTX-241 towards these HGG cell lines in comparison to normal human astrocytes (NHA) was observed, with NHA nearly insensitive to MTX-241 even at >100 µM. We found a significant inhibition of p-EGFR and p-Akt in these cell lines in comparison to DMSO controls. Further, we identified a unique glycolytic-suppressing activity of MTX-241 in the U87/DIPG lines, to a greater extent than treatment with gefitinib or alpelisib. Our data suggests that a dual inhibitor of EGFR and PI3K represents a viable therapeutic strategy in adult and pediatric HGG.